Analysis of the effectiveness of the NEC Directive on the tropospheric ozone levels in Portugal - Barros, Nelson (2021)
The National Emission Ceilings Directive 2001/81/CE (NEC Directive) was adopted in the European Community in 2001 and went through a revision process in 2005. One of its main objectives is to improve the protection of the environment and human health against the risks of adverse effects from ground-level ozone, moving towards the long-term objective of not exceeding critical levels proved to effectively protect the populations and ecosystems. Considering such objectives, national emission ceilings were established imposing the years 2010 and 2020 as benchmarks. Ten years later, what was the effectiveness of this Directive concerning the control of tropospheric ozone levels in Portugal? In order to answer the previous question, annual ozone precursors' emissions (NOx, NMVOC) and annual atmospheric concentrations (NOx and O3) were analyzed between 1990 and 2011. The background concentrations were assessed in each environment type of air quality station (urban, suburban and rural) through their annual mean ozone concentration and the hourly information threshold exceedances (episodic peak levels). To evaluate the statistical differences in the inter-annual episodic peak levels, a Peak Ozone Index (POIx) was defined and calculated. The results show that, despite the achievement on the emissions NEC Directive goals, associated to the reduction of ozone precursors' emissions, and the decrease of ozone episodic peak levels, the mean tropospheric ozone concentrations significantly increased between 2003 and 2007 (p < 0.05) although the number of exceedances to the information threshold (180 mg m3 ) has decreased. During the period of 1990e2000, before the implementation of the NEC Directive, the mean ozone values were 25% lower in rural stations, 26% in urban stations and 12% in suburban stations, demonstrating that the NEC policy based on NOx and NMVOCs emissions reduction does not lead to an effective overall reduction of ozone concentrations considering the reduction on these pollutants independently. Indeed, the mesoscale ozone production and/or the long range advection may play also an important role as the analysis of Mace Head ozone concentrations suggests. Above all, and due to its non-linear interactions in the ozone chemical balance, the NEC directive should impose emissions' reduction respecting the NOx/NMVOC ratio instead of consider it as a mere guideline value. The mesoscale photochemical ozone production should be carefully analyzed under the new policies, namely in coastal countries like Portugal where the mesoscale circulations play a crucial role in this type of phenomena.